A fluorometric skin-interfaced microfluidic device and smartphone imaging module for in situ quantitative analysis of sweat chemistry - Sekine, Yurina; Kim, Sung Bong; Zhang, Yi; Bandodkar, Amay J.; Xu, Shuai; Choi, Jungil; Irie, Masahiro; Ray, Tyler R.; Kohli, Punit; Kozai, Naofumi; Sugita, Tsuyoshi; Wu, Yixin; et al. (Lab on a chip, 2018)
The rich composition of solutes and metabolites in sweat and its relative ease of collection upon excretion from skin pores make this class of biofluid an attractive candidate for point of care analysis. Wearable technologies that combine electrochemical sensors with conventional or emerging semiconductor device technologies offer valuable capabilities in sweat sensing, but they are limited to assays that support amperometric, potentiometric, and colorimetric analyses. Here, we present a complementary approach that exploits fluorometric sensing modalities integrated into a soft, skin-interfaced microfluidic system which, when paired with a simple smartphone-based imaging module, allows for in situ measurement of important biomarkers in sweat. A network array of microchannels and a collection of microreservoirs pre-filled with fluorescent probes that selectively react with target analytes in sweat ( e.g. probes), enable quantitative, rapid analysis. Field studies on human subjects demonstrate the ability to measure the concentrations of chloride, sodium and zinc in sweat, with accuracy that matches that of conventional laboratory techniques. The results highlight the versatility of advanced fluorescent-based imaging modalities in body-worn sweat microfluidics platforms, and they suggest some practical potential for these ideas.